Determine the Effectiveness of Intranasal Splints in Preventing Nasal Adhesion - Bakht Zada, Kamran Chaudhry, Aamir Ikram, Arsalan Akhtar, Muhammad Naseem Khan, Zafar Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the effectiveness of intranasal splints in preventing nasal adhesion. Study Design: Descriptive case series Place and Duration: The study was conducted at ENT department of Lady Reading Hospital Peshawar and Chaudhary Muhammad Akram Teaching and Research Hospital, Lahore for the duration of six months April 2021 to September 2021. Methods: There were 120 participants of both sexes in this research. In this study, the patients ranged in age from 16 to 50 years old. Patient demographics, such as gender, age, and height/weight were logged with their informed written consent. During general anesthesia, a patient with a deviated nasal septum and septoplasty was selected for the procedure. Immediately following the septoplasty treatment, the patient had intra-nasal splints and nasal packing placed. The nasal packing was removed on the second postoperative day, while the nasal splints were removed on the 15th day after surgery. After a three-week follow-up, frequency of nasal adhesion was calculated. Data were analyzed 24.0. Results: Among 120 cases, 75 patients, 59.2% were between the ages of 26 and 40.The mean age of the patients was 26.34±7.51 years with mean BMI 23.07±9.44 kg/m2. Most of the cases were 67 (55.8%) male and 53 (44.2%) were females. Nasal obstruction was found among 53 (44.2%) patients, frequency of rhinorrhea was 33 (27.5%) and mixed symptoms were found in 20 (16.7%). At final follow up prevalence of nasal adhesion was found in 9 (7.5%). Conclusion: According to the findings of this study, intranasal splints were an efficient and safe treatment for preventing nasal adhesion after septoplasty.